Sonchus oleraceus Linn extract enhanced glucose homeostasis through the AMPK/Akt/ GSK-3β signaling pathway in diabetic liver and HepG2 cell culture. (February 2020) - Chen, Lei; Lin, Xiujun; Fan, Xiaoyun; Qian, Yuewei; Lv, Qiyan; Teng, Hui
Abstract: The extracts of S. oleraceus Linn (SOL) and its main phenolic compounds have shown anti-diabetic effects, but their underlying mechanisms for glucose homeostasis remain unclear. The aim of this study is to evaluate the anti-diabetic mechanism of SOL by using the streptozocin (STZ) induced diabetic rat model. When diabetic rats were fed with SOL at a dose of 400 mg/kg/day for 6 weeks, the concentrations of triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) were reduced by 43%, 22%, and 16%, respectively. Meanwhile, it was also found that daily feeding of SOL to diabetic rats led to a decrease in plasma glucose level by approximately 23%. Positive effects were observed on glucose homeostasis due to the down-regulation of AMPK/Akt/GSK-3β pathway, as indicated by the suppressions of adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), protein kinase (Akt) phosphorylation, glycogen synthase kinase 3 beta (GSK-3β), and the hepatic insulin resistance. In HepG2 cells, AMPK, Akt and GSK-3β showed a consistent transcript regulation. SOL at dose of 400 mg/kg/day feeding for 6 weeks showed a positive effect comparable to metformin. Graphical abstract: Image 1 Highlights: Major phenolics in S oleraceus Linn (SOL) was found to have intestinal stability. SOL represented a very effective role in high blood glucose. SOL regulated AMPK/Akt/GSK-3β signaling pathway in diabetic rat and HepG2.